Improving the quality of human capital as part of the development of the knowledge based economy – selected projects in the field of health care implemented under the Human Capital Operational Program - Borek-Wojciechowska, Regina; Kłokow, Sylwia (Polish Journal of Public Health, 2013)
In the economy based on knowledge, the demand for the knowledge and qualified employees is constantly growing and consequently the human capital and all of the process¬es aiming at raising the level of the human capital are be¬coming more and more important. It is particularly visible in the area of health care which due to the rapid develop-ment of medical sciences as well as demographic changes in the society requires making thought over investments in human capital. Simultaneously, one should remember that the high quality in health care sector service is one of the basic factors strengthening human capital of the entire society. The aim of the article is to introduce the projects con¬nected with the improvement in the quality of human capital in health care system, which are carried out as part of The Human Capital Operational